5 - L’impact des projets/programmes d'assistance extérieure sur le transfert des technologies aux pays en développement: le cas du Cameroun - NDONGKO, Wilfred A.; JUA, Nantang (Africa Development, 1984)
Development literature abounds with indictments that foreign a has fpr most part , been instrumental in the transfer of inappropria technology to the LDCs. Whereas this argument Is not suprious, the LD or their decision-makers are also to blame . In the case of Cameroon , development policy couched on the principles of Planned Liberalism Self-reliant Development, Balanced Development and Social Justice impelled it to adopt a two pronged approach vis-a-vis its quest for fore aid to finance projects or programmes. Thus , for projects that are inser in the Development Plans, the feasibility Studies are carried out by t technical ministry concerned-qua-Camero on government. In the alterna approach, ideas which are projects in their embryonic stage's are presented to prospective sponsors who will then decide or refuse to carry out t feasibility studies. However, all these policies are susceptible to change, depending on the political nostrum of the government in power . A cursory perusal of several aid agreements that have been entered into between Cameroon and diverse aid donors shows that most these agreements also contain «restrictive practices». Therefore if Cameroon is to curb or alleviate the deleterious effects of these practices, some policy changes and! or initiation have to be undertaken both in Camero and in donor countries. As far as Cameroon is concerned, it is impera that it begins to develop a coherent technological plan now , preferably on long-term basis . It is also imperative to review Cameroon's Investmen Code so as to buttress the effectiveness of the various measures to be ta along these policy changes. As for donor countries, given their unwilli ness to cease and desist from the practices of tying up per se, they sh be urged to adopt a «triangular approach» to these practices . This wo enable recipient countries to use the funds, obtained from a donor coun in a third country where appropriate technology might be readily avail Consequently, these practices would enhance Economic and Technical Cooperation among Developing Countries. Wilfred A. NDONGKO, Directeur de Recherche, Ministère de l'Enseignement Supérieu Recherche Scientifique, Institut des Sciences Humaines, B Yaounde/ CAMEROUN Nantang JUA, Chargé de Recherche, Ministère de l'Enseignement Supérie Recherche Scientifique, Institut des Sciences Humaines, B.P. 6170, Yaounde , CAMEROUN